2000
DOI: 10.1111/j.1471-0528.2000.tb11660.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of vaginal clindamycin for early pregnancy bacterial vaginosis

Abstract: Objective To determine whether treatment of bacterial vaginosis (BV) with vaginal clindamycin affects pregnancy outcome. Materials and methodsMothers with singleton pregnancies and without previous preterm delivery in 17 health centres in Oulu from March 1996 Until March 1998, in whom BV was diagnosed by Gram stain of a vaginal swab at the first antenatal visit (at the 12th gestational week) were randomised at Oulu University Hospital to have a one-week course of vaginal clindamycin, or placebo. A follow up sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
4

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 22 publications
3
39
0
4
Order By: Relevance
“…After randomization and treatment with clindamycin or placebo, the preterm birth rate in the clindamycin group was 13.7%, compared with 6.0% in the placebo group (OR, 2.5; 95% CI, 0.6-10). This study therefore supports the evidence that vaginal clindamycin treatment of BV in the first trimester does not reduce the risk of preterm birth 15 . In 1999, French et al 16 evaluated the association between BV, first-trimester vaginal bleeding and preterm labor in 1100 pregnant women who were enrolled in a prospective observational study (level II-II).…”
Section: Infectious Diseases In Obstetrics and Gynecology • 125supporting
confidence: 79%
See 2 more Smart Citations
“…After randomization and treatment with clindamycin or placebo, the preterm birth rate in the clindamycin group was 13.7%, compared with 6.0% in the placebo group (OR, 2.5; 95% CI, 0.6-10). This study therefore supports the evidence that vaginal clindamycin treatment of BV in the first trimester does not reduce the risk of preterm birth 15 . In 1999, French et al 16 evaluated the association between BV, first-trimester vaginal bleeding and preterm labor in 1100 pregnant women who were enrolled in a prospective observational study (level II-II).…”
Section: Infectious Diseases In Obstetrics and Gynecology • 125supporting
confidence: 79%
“…The results are similar to the conclusion of McGregor et al 13 that topical treatment in early pregnancy reduced vaginal fluid mucinase and sialidase, but failed to reduce the rate of preterm births 14 . A recent randomized controlled trial by Kurkinen-Raty et al 15 assessed the efficacy of vaginal clindamycin in reducing preterm birth (level I). Of the 1956 women without a history of preterm delivery who were screened at the first antenatal visit (gestational week 12), 143 women tested positive for BV.…”
Section: Infectious Diseases In Obstetrics and Gynecology • 125mentioning
confidence: 99%
See 1 more Smart Citation
“…Dans les études menées jusqu'ici, elle varie entre 8 et 20 % des femmes enceintes. Elle serait plus élevée dans la population nord-américaine (14 à 35 % selon les séries [8,22]) que dans la population européenne (4 à 14 % selon les séries au Royaume-Uni [12,20], 8,6 % en Autriche [26], 7,3 % en Finlande [27], 15,6 % en Suède [16]). …”
Section: Discussionunclassified
“…Even worse, Klebanoff's (Klebanoff et al, 2001) and Odendael's study (Odendaal et al, 2002) on the treatment of trichomoniasis and BV, respectively, rather demonstrated an increased risk of preterm birth after treatment with metronidazole, leading several authors to the compelling conclusion that metronidazole should not be used in pregnancy with the purpose to reduce the risk of preterm birth (Donders et al, 2009;Odendaal et al, 2002;Carey et al, 2003;Morency & Bujold, 2007). Investigators using broader spectrum antibiotics, also covering gram positive cocci and E coli, on the other hand, were successful in the reduction of preterm birth in several placebo controlled studies (Larsson et al, 2006;Lamont et al, 2003;Ugwumadu et al, 2003), although not all (Kekki et al, 2001;Kurkinen-Raty et al, 2000;Rosenstein et al, 2000). As most studies used a single treatment course of 5 to 7 days, and test of cure was not always done, one can ask whether a more intensive and repetitive treatment regimen would not be indicated, but studies are lacking.…”
Section: Intrauterine Growth Restrictionmentioning
confidence: 99%